THE INFLUENCE OF HUMAN RESOURCE QUALITY ON THE INTEGRITY OF FINANCIAL REPORTS IN COMPANIES IN EAST JAVA - Santoso H.P; Juita M.V (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to examine and analyze the influence of Human Resources (HR) quality on the integrity of financial reports in companies operating in East Java. Financial report integrity is crucial for ensuring transparency and stakeholder trust, but its effectiveness is highly dependent on the competence and ethics of the workforce. The research method used is quantitative with an associative approach. Data was collected through questionnaires distributed to 70 respondents consisting of accounting staff and financial managers. The data analysis technique used Partial Least Square (PLS). The results show that HR quality, as measured by the dimensions of competence, experience, and professional commitment, has a positive and significant effect on financial report integrity. This finding indicates that companies with HR with high ethical standards and a deep understanding of accounting tend to produce accurate financial reports free from material misstatement. This study recommends improving capacity development and continuous training for finance staff in East Java.